-related autosomal recessive encephalopathy in 2 Turkish children. - Yaramis, Ahmet; Lochmüller, Hanns; Topf, Ana; Sonmezler, Ece; Yilmaz, Elmasnur; Hiz, Semra; Yis, Uluc; Güngör, Serdal; Ipek Polat, Ayse; Edem, Pinar; Beltran, Sergi; Laurie, Steven; et al. (Neurol Genet, 2020)
Objective: This study presents the neurologic phenotypes of 2 brothers with a novel homozygous mutation that was identified in a large Turkish consanguineous cohort of neurogenetic diseases. Methods: Whole-exome sequencing and bioinformatic analysis of consanguineous families with children affected by early-onset, neurogenetic disorders was performed using the RD-Connect Genome-Phenome Analysis Platform. We also performed clinical, EEG, and neuroimaging analyses in unaffected siblings and parents. Results: We have identified a homozygous missense mutation in (p.Gly1278Ser, NM_001845.5:c.3832G>T) in 2 siblings affected by small vessel brain disease with periventricular leukoencephalopathy and ocular defects. Presenting symptoms included mild weakness, hemiparetic gait, pyramidal findings, and seizures, whereas their intellectual and behavioral functions were normal. Both parents and 5 of the siblings (3 boys and 2 girls) were heterozygous for the variant. They did not show any clinical or laboratory signs of small vessel disease. Conclusions: has previously been associated with dominant small vessel disease of the brain and other organs, manifesting with high penetrance in heterozygous mutation carriers. Our findings provide evidence that -related encephalopathy can be inherited in an autosomal recessive manner, which is important for counseling, prognosis, and treatment. Genotype-phenotype correlations remain to be established.